Ke Arah Impian Menggapai Taraf Universiti Penyelidikan di Malaysia: Kajian Kes Universiti Malaysia Sabah - Yazid, Mohd Noor Mat; Idris, Asmady (ASPENSI in Bandung, Indonesia, 2008)
ABSTRACT: The Ministry of Higher Education of Malaysia has recently called for all public universities in Malaysia to focus more on research activities. This call is to ensure that a high quality standard of research can be achieved in order to produce more research universities in the future. Accordingly, Malaysia University of Sabah (UMS), as the ninth public university in Malaysia, has enthusiastically answered this call by encouraging and facilitating its academic staff to actively engage in research activities. UMS, however, realizes that it will take a long process before it can be regarded as a research university. Therefore, this article has identified six pro-active actions that may be taken by UMS to achieve its vision i.e. (1) strengthen physical needs; (2) increase the number of postgraduate students; (3) acquire more highly qualified needs; (3) acquire more highly qualified academicians; (4) enhance international networking; (5) form several research leaders or âMalim Sarjanaâ; and (6) publish and commercialize research outcomes in highly refereed journals and commercial sectors. Especially the latest, UMS should cooperate in publishing sector with some foreign universities to make its name is acknowledged and well-known by international world. Without the effort of productive and qualified publication, this beautiful and prominent infrastructure will not contribute to establishing a pioneer and superior university in research field.Key words: the policy on research university in Malaysia, challenge and respond of UMS, and some actions should be taken by UMS. Â Â Â Â About the Authors: Prof. Madya Dr. Mohd. Noor Mat Yazid ialah Pensyarah pada Program Antarabangsa, Sekolah Sains Sosial UMS (Universiti Malaysia Sabah). Beliau menyambung ke peringkat Sarjana dalam bidang Hubungan Antarabangsa di University of Leeds, England, tahun 1997; dan Ijazah Doktor Falsafah dalam bidang yang sama di University of Birmingham, England, tahun 2004. Beliau menulis buku, di antaranya adalah Hegemonic Powers, Radical Politics and Developmental States: The Case of Indonesia â Malaysia Political Relations during the Cold War (Kota Kinabalu: Penerbit UMS, 2007). Prof. Madya Dr. Asmady Idris ialah Pensyarah dan Dekan Sekolah Sains Sosial UMS. Beliau menamatkan Ph.D. (Doctor of Philosophy) dari University of Newcastle upon Tyne, UK (United Kingdom), dengan menulis Ph.D. thesis mengenai: âKey Determining Factors Influencing Small Statesâ Relationships: A Case Study of Malaysiaâs Relations with Saudi Arabiaâ. Beliau menulis buku, di antaranya adalah Amerika Syarikat: Satu Kuasa Hegemoni Dunia (Kuala Lumpur: Dewan Bahasa dan Pustaka, 2000). Beliau boleh dihubungi dengan alamat e-mail: drasmadyi@gmail.comHow to cite this article? Yazid, Mohd Noor Mat & Asmady Idris. (2008). âKe Arah Impian Menggapai Taraf Universiti Penyelidikan di Malaysia: Kajian Kes Universiti Malaysia Sabahâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.1, No.2 [November], pp.249-260. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112.Chronicle of the article: Accepted (September 17, 2008); Revised (October 25, 2008); and Published (November 20, 2008).